Pathways to Electric Mobility in the Sahel : Two and Three-Wheelers in Bamako and Ouagadougou - Arroyo-Arroyo, Fatima; Vesin, Vincent (World Bank, Washington, DC, 2022)
This study analyzes the potential for electrification of two- and three-wheelers in Sahelian cities, using Bamako and Ouagadougou as case studies. The electrification of urban mobility in the Sahel has the potential to address pressing development issues such as reducing local air pollution, decarbonizing the transport sector, reducing vulnerability to petrol imports, and creating new jobs. The study has a particular focus on the electrification of two- and three- wheelers due to their dominant share of total mobility in Sahelian cities. In Ouagadougou, two-wheelers are used mostly for private vehicle use. In Bamako, they are used for private travel as well as commercial passenger travel as mototaxis and freight transport. Several international experiences show that switching from internal combustion engines to electric twoand three-wheelers has a high potential to reduce local air pollution and carbon dioxide (CO2) emissions as well as noise pollution. The World Bank aims to develop a dialogue with the governments of the Sahel region regarding the transition to two- and three-wheelers in cities, and consequently the reduction of carbon emissions, air pollution and dependence on fossil fuels. Based on the analysis of the mobility situation in the cities of Ouagadougou and Bamako, independent recommendations were prepared on how to develop a roadmap for transformation to e-mobility in Sahelian cities. The study focuses on all types of two- and three-wheeled vehicles, both motorized and nonmotorized. Thus, in addition to scooters, motorcycles and tricycles, bicycles are also included in the study. Similarly, the study considers two- and three-wheeled vehicles for the transport of people and goods.